Optimization of InAs quantum dots through growth interruption on InAs/GaAs quantum dot heterostructure - Tongbram, B.; Ahmad, A.; Sengupta, S.; Mandal, A.; Singhal, J.; Balgarkashi, A.; Chakrabarti, S. (Journal of luminescence, 2017)
This study investigates the optical and structural properties of multilayer InAs QDs heterostructures designed with varying levels of growth interruption. Samples were subject to growth interruptions of 0, 25, 50, and 75s (samples A, B, C, and D, respectively). Low-temperature (9K) photoluminescence (PL) experiments revealed an initial redshift in the ground-state emission peak (from 1131 to 1145nm) as growth interruption (GI) was varied from 0 to 25s. In addition, we observed a blueshift (from 1145 to 1100nm) when the interruption lasted for more than 25s. The thermal activation energies of samples A–D, calculated from temperature-dependent (8–300K) PL experiments, were approximately 182.4, 241.5, 206.2 and 175.3meV, respectively. The photoluminescence excitation (PLE) studies reveal the existence of two strong peaks at each detection energy, one at ~ 63meV and other at ~ 140meV. These two PLE peaks arise from the InAs QDs shifting toward the higher energy (meV) levels which have lower intensities with the increase of GI. Longer GI time increases the intensities of InAs wetting layer as well as GaAs matrix. This, in turn, worsens the optical property. In our structural study, high-resolution transmission electron microscopy (HRTEM) confirmed that a short interruption (25s, Sample B) in the growth of QDs produced a better size homogeineity. We also observed that Sample B has a tensile stress along the growth direction (001), which increased the height of the InAs QDs to approximately 8nm with the interplanar distance of 0.626Å along the 001 planes. In addition, the InAs QDs maintained their geometrical shape till 50s and the shape of the dots started deterioting after 50s as a result of the decrease in QDs height of 2nm revealed from HRTEM. In contrast, high-resolution X-ray diffraction (HRXRD) found the strain energy drastically dropped to 0.4765meV/atoms (75s, Sample D) from 0.819meV/atoms (25s, Sample B), showing inhomegenous QDs size distribution. Higher strain energy of 0.819meV in the stacked heterostructure improved QDs size homogeineity. The average indium content calculated from the out-plane HRXRD in samples A–D were 0.234%, 0.288%, 0.241%, and 0.218%, respectively. From the growth model, we noticed a significant change in the surface self-diffusion rate of indium adatoms. The indium adatoms migration to larger adjacent QDs is higher when the pre-matured QDs lie within the critical distance (X; ~ 30nm). At X > 30nm, the QDs start strinking, thereby reducing the height of QDs. Thus, this paper shows how our growth method helps in optimizing the QDs homogeineity and increasing the QDs dimension. Cross-sectional TEM images of sample B (growth interruption time 25s) along with sample D (growth interruption time 75s). [Display omitted]